Mary of Nazareth [videorecording (DVD)] : a mother's life - Morrow, Don, 1927- (Biography (A & E Home Video (Firm)), 2005)
This video presents an amazing story of the woman hailed as the Blessed Virgin and Mother of God--Mary of Nazareth.